Accuracy of echocardiographic estimations of right heart pressures in adult heart transplant recipients. Issue 7 (22nd April 2022) - Sridharan, Aadhavi; Dehn, Monica M.; Cooper, Craig; Madineedi, Vidya S.; Ordway, Linda J.; DeNofrio, David; Patel, Ayan R.
Abstract: Background: Accurate assessment of right atrial pressure (RAP) and pulmonary artery systolic pressure (PASP) is critical in the management of heart transplant recipients. The accuracy of echocardiography in estimating these pressures has been debated. Objective: To assess the correlation and agreement between echocardiographic estimations of right heart pressures with those of respective invasive hemodynamic measurements by right heart catheterization (RHC) in adult heart transplant recipients. Methods: This is a prospective evaluation of 84 unique measurements from heart transplant recipients who underwent RHC followed by standard echocardiographic evaluation within 159 ± 64 min with no intervening medication changes. The relationship between noninvasive pressure estimations and invasive hemodynamic measurements was examined. Results: Mean RAP was 7 ± 5 mmHg and mean PASP was 33 ± 8 mmHg by RHC. There was no significant correlation between echocardiographic estimation of RAP and invasive RAP (Spearman's rho = −0.05, p  = .7), and no significant agreement between these two variables (weighted kappa = −0.1). There was a modest correlation between echocardiographic estimation of PASP and invasive PASP ( r  = .39, p  = .002). Bland‐Altman analysis showed a mean bias of 2.1 ± 9 mmHg (limits of agreement = −15 to 20 mmHg). Conclusion: In heart transplant recipients, there is no significant correlation or agreement between echocardiographic RAP estimation and invasively determined RAP. Noninvasive PASP estimation correlates significantly but modestly with invasively measured PASP. Further refinement of echocardiographic methods for assessment of RAP is warranted in this unique patient population.